First Experiences in Using STACK in Education of Circuit Analysis at University of Vaasa - Ellonen, Otto; Vesapuisto, Maarit; Vekara, Timo (IEEE, 2022)
The first compulsory courses in circuit analysis for the technology students at University of Vaasa create an important basis for the studies on Electrical Engineering. Here, the particular challenge for teaching has proven to be the creation of a new way of thinking for students, who have used memorization as their primary learning method. The first-year students have a heterogeneous starting level in knowledge and skills. This paper focuses on the positive experiences received at the University of Vaasa from utilizing visualisation, interactivity, repetition and testing in learning in an environment called STACK (System for Teaching and Assessment using a Computer algebra Kernel) which operates in the web browser. We have developed simple and representative problems of circuit analysis which, through repetition, introduces students into a new way of thinking and subjects them into deep learning. Additionally, the problems can be solved regardless of time and place, even in one’s own personal pace. At the end of the course, feedback on using STACK has been collected from the students. It has been almost entirely positive, and more problems have been desired. It is found that students that did more exercises also passed the course with better grades.
Keywords: circuit analysis; education; interactivity; JSXGraph; STACK; visualization; fi=Sähkötekniikka|en=Electrical Engineering|